2022
DOI: 10.3390/mi13040521
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Drone in Virtual Reality Using MEMS Sensor Technology and Machine Learning

Abstract: In recent years, drones have been widely used in various applications, from entertainment, agriculture, their use in photo and video services, military applications and so on. The risk of accidents while using a drone is quite high. To meet this risk, the most important solution is to use a device that helps and simplifies the control of a drone; in addition, the training of drone pilots is very important. To train the drone pilots, both physical and virtual environments can be used, but the probability of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Ref. [40] found that an intelligent flight assistant based on the simplest neural network architecture has the capacity to outperform human flight performance. Refs.…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…Ref. [40] found that an intelligent flight assistant based on the simplest neural network architecture has the capacity to outperform human flight performance. Refs.…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…A method for controlling a drone in virtual reality using machine learning and MEMS sensor technology is proposed in [25]. In order to predict the drone's motion, the authors use an IMU (Inertial Measurement Unit) to capture the drone's motion in three-dimensional space.…”
Section: Machine Learning Techniques In Drone Controlmentioning
confidence: 99%
“…The authors conclude that the memory-based strategy is a promising approach for UAVs with limited environmental knowledge to avoid obstacles. System can detect individuals and their distances in real-time to ensure social distance rules are followed [23] Analyzing drone data using machine learning methods Three stages: data acquisition, data processing, and data analysis Proposed framework and machine learning methods provide an efficient and effective method for continuing the investigation into drone-related incidents [24] Evaluating reinforcement learning and deep learning algorithms for controlling UAVs in various tasks Simulated environments and various metrics Deep learning models generally have higher accuracy and generalization, but each algorithm performs differently depending on the task and environment [25] Controlling a drone in virtual reality using machine learning and MEMS sensor technology IMU to capture drone motion in 3D space Machine learning algorithm accurately predicts drone motion, could be utilized for virtual reality drone control and training/simulation [26] Using RF signals to find and identify drones…”
Section: Machine Learning Techniques In Drone Controlmentioning
confidence: 99%
“…Accelerometers based on micro-electro-mechanical system (MEMS) are extensively applied in inertial integrated navigation systems, mobile vehicles and smart robotics [1][2][3]. They have also been used for in vivo monitoring in biomedical field, image stabilization device in portable camera, and virtual reality (VR) technology [4][5][6]. Based on their working principles, MEMS accelerometers can be classified into several categories, such as piezoresistive ones, capacitive ones, and tunnel effect ones [7].…”
Section: Introductionmentioning
confidence: 99%